The book of (more) delights eaudiobook Essays. - Gay, Ross (2023)
From bestselling author of The Book of Delights and award-winning poet, a book of lyrical mini-essays celebrating the everyday that will inspire readers to rediscover the joys in the world around us. Ross Gay's essays have been called "exquisite" (Tracy K. Smith), "imperative" (the New York Times Book Review ), and "brilliant" (Ada Limón). Now, in this new collection of genre-defying pieces, again written over the course of a year, one of America's most original voices continues his ongoing investigation of delight. For Gay, what delights us is what connects us, what gives us meaning, from the joy of hearing a nostalgic song blasting from a passing car to the pleasure of refusing the "ubiquitous, nefarious" scannable QR code menus, from the tiny dog he fell hard for to his mother baking a dozen kinds of cookies for her grandchildren. As always, Gay revels in the natural world—sweet potatoes being harvested, a hummingbird carousing in the beebalm, a sunflower growing out of a wall around the cemetery, the shared bounty from a neighbor's fig tree—and the trillion mysterious ways this glorious earth delights us. For his many fans eagerly awaiting this new volume and for readers who have enjoyed the works of Aimee Nezhukumatathil, Zadie Smith, and Rebecca Solnit, Gay once again offers us "literature that feels as fluent and familiar as a chat with a close friend" (the New York Review of Books ). The Book of (More) Delights is a collection to savor and share.